Financial Performance of Supermarkets in Karnataka (Global Journal of Management and Business Research, 2013)
Global supermarket food products sales are predicted to generate revenue in excess of $1.70 trillion by 2015, according to research from Global Industry Analysts. Market growth has been driven by the rising importance of consumerism. Since supermarkets first appeared in the US, they have been rolled out all over the globe, with supermarket chains securing their place at the top of the world#x2019;s retail chain. Due to the effects of the economic recession, the number of consumer visits to supermarkets has fallen over recent years. Currently the UK is undergoing a sustained period of retail growth, with the high level of consumer confidence witnessed in previous years holding up. However, this situation is fragile and could change rapidly. Slower earnings, coupled with speculation about changes in interest rates and job insecurity could affect the rate of growth. Consequently retailers will suffer from even a minor economic downturn as profit margins have already been cut to sustain levels of sales. Overall, however, it is apparent that many retailers are committed to expansion with many new sites due to open over the next few years. India, with its large, young, and growing population, presents an attractive target for expanding supermarket chains, especially from other less-developed countries. India is attractive to foreign retailers demographically and perhaps economically. Even the local marketers in the developing countries are renovating their traditional shops into a modern supermarket. With this regards an attempt has been made to understand the financial performance of supermarkets (both traditional